2014
DOI: 10.1021/am501336u
|View full text |Cite
|
Sign up to set email alerts
|

Construction of ZnO/ZnS/CdS/CuInS2Core–Shell Nanowire Arrays via Ion Exchange: p–n Junction Photoanode with Enhanced Photoelectrochemical Activity under Visible Light

Abstract: ZnO/ZnS/CdS/CuInS2 core-shell nanowire arrays with enhanced photoelectrochemical activity under visible light were successfully prepared via ion exchange and hydrothermal methods. The samples were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, UV-vis absorption, X-ray photoemission spectroscopy, and photoelectrochemical response. As a p-n junction photoanode, ZnO/ZnS/CdS/CuInS2 heterostructure shows much higher visible light photoelectrocatalytic activity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(57 citation statements)
references
References 38 publications
3
54
0
Order By: Relevance
“…Compared with chalcopyrite CuInS 2 , the wurtzite CuInS 2 showed a higher and broader absorption in the entire visible region and near-infrared region. The bandgap can be determined by plotting (αhν) 2 versus hν (α = absorbance, h = Planck's constant, and ν = frequency) [26,27]. As shown in the inset picture, the calculated optical bandgap for chalcopyrite and wurtzite CuInS 2 is about 1.54 and 1.47 eV, respectively, which is close to the bulk energy bandgap of CuInS 2 .…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Compared with chalcopyrite CuInS 2 , the wurtzite CuInS 2 showed a higher and broader absorption in the entire visible region and near-infrared region. The bandgap can be determined by plotting (αhν) 2 versus hν (α = absorbance, h = Planck's constant, and ν = frequency) [26,27]. As shown in the inset picture, the calculated optical bandgap for chalcopyrite and wurtzite CuInS 2 is about 1.54 and 1.47 eV, respectively, which is close to the bulk energy bandgap of CuInS 2 .…”
Section: Resultsmentioning
confidence: 82%
“…In the previous studies, CuInS 2 has been found to exist in three different crystal structures: chalcopyrite, zinc blende, and wurtzite [4][5][6]. Chalcopyrite CuInS 2 is the most common existing phase at room temperature, whereas those with zinc blende and wurtzite structures are stable only at high temperatures.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For the ZnO/ZnO nanowire/nanoparticle formation, the HRTEM images (Fig. 3(c)) exhibit many ZnO nanoparticles on the surface of the nanowires (with the lattice spacing of 0.26 and 0.28 nm, respectively, for the ZnO (002) and (100) planes [32,33]). Then, after the hydrothermal process, hierarchically branched ZnO nanowire arrays are successfully synthesized (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] The oxygen evolution reaction (OER) is the key to renewable-energy technologies, such as rechargeable metal-air batteries and water splitting. Water oxidation has an important function in the storage of energy, such as in solar fuel synthesis.…”
Section: Introductionmentioning
confidence: 99%